Assessing the Performance of Egypt's Seed Sector - Thijssen, Marja H.; Bishaw, Zewdie; Ahmed, Hamdino; Gupta, Arnab (Wageningen University & Research, 2023)
The current study shows the results of an assessment of the performance of the seed sector in Egypt. It elaborates bottlenecks and ambitions towards the development of a well-functioning seed sector that is innovative, competitive, resilient and inclusive. Since seed system configurations vary among crops groups and even crops, it zooms in on seed systems of cereals, food legumes and vegetables, and subsequently synthesizes seed sector challenges and ambitions at sector level. The assessment has been implemented through desk study and a consultative process with key seed sector stakeholders. It was implemented by Wageningen University & Research, ICARDA and an Egyptian seed sector consultant. The study provides entry points for the design of partnerships between Egypt and the Netherlands on seed sector transformation.